Monitoring The Photovoltaic Industry Financing Challenge in Iran - Zargar, Batoul; Jahangirnia, Hosein; Emami Meibodi, Ali; Safa, Mozhgan (International Journal of Sustainable Construction Engineering and Technology, 2023)
The global energy crisis has increased the need to use renewable energy such as solar energy instead of fossil fuels. The present study aims to model the financing of the photovoltaic industry which is one of the most fundamental challenges that this industry is facing. To fulfill this aim, this study proposed a model based on the opinions of industry experts collected through interviews in the period from January 2021 to August 2021 and validated it by the structural equation modeling method. Based on the results of the research, issues related to the financing challenge of the photovoltaic industry can be examined in 8 clusters, which are; challenging factors, mediating conditions, consequences, government financing strategies, government incentives for the private sector, personal financing strategies, public financing strategies, guarantees, and insurance. The relationship between each of these variables has also been confirmed as research hypotheses.